Increase in Prices of Basic Ingredients on Food Availability After the 2024 Election - Prayuda, Ramanda Bima; Kelana, Mukhamad Bayu; Mufidah, Naila; Apandi, Ade; Uddin, Hafiz Rafi (MultiTech Publisher, 2024)
The focus of this writing is to discuss the complexity of post-election increases in staple food prices which have a significant impact on food availability and social stability in Indonesia. In this context, research analyzes the impact of increases in staple food prices on post-election food availability and the measures that can be taken Done to overcome it. Qualitative methods with a literature study approach were used In this research, by collecting secondary data from various sources including journals, books and official government websites. Phenomenon analysis is carried out by interpreting data which describes the role of the researcher as a key instrument. The author identifies that post-election increases in staple food prices could have a significant negative impact Especially for lower middle economic groups. The impacts include social instability, increased poverty levels, and negative influences on other economic sectors. Therefore, appropriate action from the government and relevant stakeholders is needed to maintain price stability and food availability. With the right steps, it is hoped that the negative impact of the post-election increase in food prices will be avoided can be minimized, so that people still have adequate and affordable access Towards food. This research provides important insights for stakeholders in facing the challenges of post-election food price increases and maintaining food stability in Indonesia.